REQUIREMENTS AND EXPECTATIONS OF MASTER’S DEGREE STUDY IN EDUCATIONAL ADMINISTRATION, SHINAWATRA UNIVERSITY - Jenkwao, Sarisa; Jenkwao, Sawien; Ratanapitakdhada, Chookwan; Yorddamnern, Somporn; Sintuaree , Jeerath (Journal of MCU Nakhondhat, 2024)
This research aimed to 1) Study opinions on the educational management of Master's degree in Educational Administration 2) Study the requirements for study Master's degree in Educational Administration, Shinawatra University 3) Study expectations for study Master's degree in Educational Administration, Shinawatra University. The data sources used in this research were teachers in the schools in Bangkok and surrounding areas 205 individuals and simple sampling random. The tool used as a questionnaire. The Index of Item Objective Congruence was obtained between 0.60 - 1.00. The reliability for the whole was 0.91. The statistics used in data analysis include frequency, percentage, mean, standard deviation and content analysis. The research results found that 1) Opinions on the educational management of Master's Degree in Educational Administration, Shinawatra University, It found that most respondents had opinions about the appropriate time of day for organizing teaching and learning as Saturday-Sunday from 8:30 a.m. - 4:30 p.m., studying mostly online and sometimes in class. The course has been certified by the teachers council of Thailand and interested in pursuing a Master's degree in Educational Administration, Shinawatra University. 2) Requirements for Master's degree study in Educational Administration, Shinawatra University. It found that overall was at the highest level. When considering each aspect from highest average in order curriculum specific information, development of special students’ characteristics, and general information of curriculum. 3) Expectations for Master's degree study in Educational Administration, Shinawatra University. It found that overall was at the highest level. When considering each aspect from the highest averages in order curriculum specific information, development of special students’ characteristics, and general information of curriculum.